2021
DOI: 10.1126/sciadv.abc7409
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NLRP3 inflammasome prevents ovarian aging

Abstract: Inflammation is a hallmark of aging and is negatively affecting female fertility. In this study, we evaluate the role of the NLRP3 inflammasome in ovarian aging and female fertility. Age-dependent increased expression of NLRP3 in the ovary was observed in WT mice during reproductive aging. High expression of NLRP3, caspase-1, and IL-1β was also observed in granulosa cells from patients with ovarian insufficiency. Ablation of NLRP3 improved the survival and pregnancy rates and increased anti-Müllerian hormone l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 45 publications
(64 reference statements)
1
70
0
Order By: Relevance
“…Inflammation detrimentally affects reproductive physiology and female fertility. In a recent study (Navarro-Pando et al, 2021) NLRP3 was found to be increased in the ovary of aged mice. Increased expression of NLRP3 and other key downstream markers, caspase-1 and IL-1b, were also detected in granulosa cells from patients with primary ovarian insufficiency.…”
Section: B Nod-like Receptor Family Pyrin Domain Containing 3 Pathology By Organmentioning
confidence: 85%
“…Inflammation detrimentally affects reproductive physiology and female fertility. In a recent study (Navarro-Pando et al, 2021) NLRP3 was found to be increased in the ovary of aged mice. Increased expression of NLRP3 and other key downstream markers, caspase-1 and IL-1b, were also detected in granulosa cells from patients with primary ovarian insufficiency.…”
Section: B Nod-like Receptor Family Pyrin Domain Containing 3 Pathology By Organmentioning
confidence: 85%
“…We presently observed not only a similar pattern of cellular expression for NLRP3 but also the upregulation of NLRP3 inflammasome components during D. These findings corroborate previous results from Zhang and colleagues suggesting the involvement of NLRP3 in inflammatory events during ovulation in mice ( Zhang et al, 2019 ). Moreover, NLRP3 was recently characterized as an important mediator of ovarian pathology during aging ( Navarro-Pando et al, 2021 ). Finally, the involvement of NLRP3 inflammasome in ovarian inflammatory response in obese mothers is supported by previous reports showing NLRP3 inflammasome activation in proinflammatory conditions like PCOS ( Wang et al, 2017 ; Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional autophagy has also been linked to ovarian insufficiency due to inflammatory aging and miscarriage, as well as to male infertility. For example, inhibition of the NLRP3 inflammasome leads to increased levels of autophagy markers in the ovary of 12‐month‐old female mice and is linked to improved reproductive pregnancy rate (Navarro‐Pando et al , 2021 ), whereas pharmacological induction of autophagy (by rapamycin) promotes endometrium autophagy (and NK cell infiltration), thus decreasing the risk of spontaneous abortion in mice (Lu et al , 2020 ). In addition, functional autophagy sustains correct spermiogenesis.…”
Section: Reproductive System Dysfunctionsmentioning
confidence: 99%